Comparison of rectal volume definition techniques and their influence on rectal toxicity in patients with prostate cancer treated with 3D conformal radiotherapy: a dose-volume analysis - Onal, Cem (BioMed Central, 2009)
BACKGROUND: To evaluate the impact of four different rectum contouring techniques and rectal toxicities in patients with treated with 3D conformal radiotherapy (3DCRT). METHODS: Clinical and dosimetric data were evaluated for 94 patients who received a total dose 3DCRT of 70 Gy, and rectal doses were compared in four different rectal contouring techniques: the prostate-containing CT sections (method 1); 1 cm above and below the planning target volume (PTV) (method 2); 110 mm starting from the anal verge (method 3); and from the anal verge to the sigmoid flexure (method 4). The percentage of rectal volume receiving RT doses (30–70 Gy) and minimum, mean rectal doses were assessed. RESULTS: Median age was 69 years. Percentage of rectal volume receiving high doses (≥ 70 Gy) were higher with the techniques that contoured smaller rectal volumes. In methods 2 and 3, the percentage of rectal volume receiving ≥ 70 Gy was significantly higher in patients with than without rectal bleeding (method 2: 30.8% vs. 22.5%, respectively (p = 0.03); method 3: 26.9% vs. 18.1%, respectively (p = 0.006)). Mean rectal dose was significant predictor of rectal bleeding only in method 3 (48.8 Gy in patients with bleeding vs. 44.4 Gy in patients without bleeding; p = 0.02). CONCLUSION: Different techniques of rectal contouring significantly influence the calculation of radiation doses to the rectum and the prediction of rectal toxicity. Rectal volume receiving higher doses (≥ 70 Gy) and mean rectal doses may significantly predict rectal bleeding for techniques contouring larger rectal volumes, as was in method 3.